2011
DOI: 10.1021/jo102572x
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity and Activation Strain Analysis of [3 + 2] Cycloaddition Reactions between Group 14 Heteroallenes and Triple Bonds

Abstract: We have computationally explored the trend in reactivity of [3 + 2] cycloaddition reactions between H(2)E=C=PH and HC≡CH as the terminal position in the phosphaallene is varied along E = C, Si, Ge, Sn, Pb. The reaction barrier drops significantly from E = C (nearly 50 kcal/mol) to E = Si-Pb (ca. 20 kcal/mol). Activation strain analyses tie this trend to a reduction in activation strain in the heavier phosphaallene analogues which, in contrast to the parent compound H(2)C=C=PH, do already possess the bent geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 49 publications
7
19
1
Order By: Relevance
“…Interestingly, these results differ, for instance, from those of Fernández et al. on the [3+2] cycloaddition reactions between Group 14 heteroallenes and acetylene 11a. They found that the energy to deform the reactants to the transition‐state geometry represented the major factor in controlling the barrier heights; a difference probably associated with the already‐bent geometry of the fragment of [ 1 ] + that interacted with the alkyne in the present case.…”
Section: Resultscontrasting
confidence: 95%
“…Interestingly, these results differ, for instance, from those of Fernández et al. on the [3+2] cycloaddition reactions between Group 14 heteroallenes and acetylene 11a. They found that the energy to deform the reactants to the transition‐state geometry represented the major factor in controlling the barrier heights; a difference probably associated with the already‐bent geometry of the fragment of [ 1 ] + that interacted with the alkyne in the present case.…”
Section: Resultscontrasting
confidence: 95%
“…However, it inverts at a certain point along the reaction coordinate and becomes more and more stabilized as one approaches the TS region. This behavior resembles that found not only for related cycloaddition reactions,, but also for other pericyclic reactions, such as double‐group transfer reactions, Alder–ene reactions, or ene–ene–yne cyclizations, and is different for other processes, such as S N 2 reactions, in which the Δ E int term is stabilizing along the entire reaction coordinate. Nevertheless, stabilization provided by the interaction term cannot compensate for the strong destabilizing effect of the deformation energy required to adopt the TS geometry (Δ E strain ), which, in turn, becomes the major factor that controls the activation barriers of the [4+2]‐cycloaddition reactions involving these geodesic polyarenes.…”
Section: Resultssupporting
confidence: 75%
“…To get more information about the underlying interactions, we have additionally analyzed all (3 + 2) cycloadditions discussed above with the distortion/interaction or activation‐strain model . These models have successfully been applied to different pericyclic reactions , , . While the analysis for all transition states is given in the Supporting Information, Figure summarized the distortion/interaction analysis for four representative examples.…”
Section: Resultsmentioning
confidence: 99%